2021
DOI: 10.30919/es8d591
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Super-Toughened PLA/CPU Blends via One-step Dynamic Vulcanization

Abstract: In this study, a serious of super-toughened poly(lactic acid) (PLA)/cross-linked polyurethane (CPU) blends were prepared via one-step dynamic vulcanization of PLA, polyethylene glycol (PEG) and isophorone diisocyanate trimer (IPDIT). FTIR and gel tests displayed that CPU was successfully generated during the dynamic vulcanization reaction. The scanning electron microscopy (SEM) images of cryo-fractured and impacted surfaces showed that the PLA/CPU blends had no obvious phase separation, which indicated good co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Toughness is a physical quantity that evaluates the ability of a material to absorb energy during plastic deformation and fracture. , In the organic sector, for example, graphene oxide (GO) has inherent toughness and stiffness, and researchers have achieved superb mechanical toughness by surface treating GO or by electrostatically self-assembling core–shell hybrid particles with other nanoparticles as fillers. , It is a combination of material strength and plasticity. The characters after fracture are obvious macroscopic plastic deformation and jagged-shaped breakage.…”
Section: Mechanical Performancesmentioning
confidence: 99%
“…Toughness is a physical quantity that evaluates the ability of a material to absorb energy during plastic deformation and fracture. , In the organic sector, for example, graphene oxide (GO) has inherent toughness and stiffness, and researchers have achieved superb mechanical toughness by surface treating GO or by electrostatically self-assembling core–shell hybrid particles with other nanoparticles as fillers. , It is a combination of material strength and plasticity. The characters after fracture are obvious macroscopic plastic deformation and jagged-shaped breakage.…”
Section: Mechanical Performancesmentioning
confidence: 99%
“…Polymer blending is an efficient and cost-effective process to prepare polymeric materials with desired mechanical properties, as well as ease of processability and printability. The development of FDM filament feedstocks from new polymer blends for FDM has been of great interest, as they often offer enhanced material performances and particularly unique functionalities when compared to their corresponding homopolymers. For instance, the study of Geng et al demonstrated that the blending of PLA and PC markedly improved the filament processability as well as FDM printability, with the resulting polymer blend filaments.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the great environmental impact that conventional petroleum-based polymers promote during its production, more and more biodegradable polymers based on renewable sources (biopolymers) arouse interest [1][2][3][4] in the production of new polymeric systems. Using of these biomaterials, considered eco-friendly, has been gaining prominence in the specialized polymers literature, in the polymeric blends processing, 3,[5][6][7] reactive mixtures, [8][9][10] composites and polymeric nanocomposites, [11][12][13][14][15] for instance.…”
Section: Introductionmentioning
confidence: 99%